2021
DOI: 10.3390/children8100840
|View full text |Cite
|
Sign up to set email alerts
|

A National Population Cohort Study Showed That Exposure to General Anesthesia in Early Childhood Is Associated with an Increase in the Risk of Developmental Delay

Abstract: This study investigated the relationship between exposure to general anesthesia (GA) and the risk of cognitive and mental disorders. This study has thus investigated the relationships between exposure to GA before the age of 3 and subsequent cognitive and mental disorders in a national-wide research sample. We obtained our subjects from the National Health Insurance Research Database (NHIRD) of Taiwan, which was based on the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…The recommendation cited animal studies showing neuronal toxic effects and pediatric studies reporting conflicting results of the effect of anesthesia in children younger than 3 years of age on neurocognitive development, learning abilities, and behavioral issues. More recent or larger pediatric study cohorts continue to leave uncertainties about the effects of anesthesia on long‐term neurodevelopment (Walkden et al, 2020; Warner et al, 2018; Yang et al, 2021; Zaccariello et al, 2019). In addition to the focus of these pediatric studies on the effect of anesthesia exposure before 3 years of age, it was not feasible based on the study design to examine the effects of anesthesia on an existing, underlying neurodevelopmental or neurodegenerative disorders where neurocognitive and behavioral dysfunctions are major components of the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendation cited animal studies showing neuronal toxic effects and pediatric studies reporting conflicting results of the effect of anesthesia in children younger than 3 years of age on neurocognitive development, learning abilities, and behavioral issues. More recent or larger pediatric study cohorts continue to leave uncertainties about the effects of anesthesia on long‐term neurodevelopment (Walkden et al, 2020; Warner et al, 2018; Yang et al, 2021; Zaccariello et al, 2019). In addition to the focus of these pediatric studies on the effect of anesthesia exposure before 3 years of age, it was not feasible based on the study design to examine the effects of anesthesia on an existing, underlying neurodevelopmental or neurodegenerative disorders where neurocognitive and behavioral dysfunctions are major components of the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have delineated the details of a representative database of 1,000,000 subjects randomly sampling from the National Health Insurance Research Database. It includes the patients’ background characteristics such as gender, date of birth, disease diagnosis, medical information, medicine prescriptions, clinical visits, or hospitalizations, which are provided to the public for research purposes [ 30 , 40 , 41 ]. Additionally, there were no statistically significant differences in age, gender, and healthcare costs between the samples and all enrollees [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the safety of GA has become an essential health issue of interest to the public and government agencies [ 29 ]. Notably, we had reported that children exposed to GA early, before age three, had a small association with an increased risk of developmental delay after that [ 30 ]. Furthermore, in an animal study exposed to postnatal GA, adult mice have chronically exacerbated fear behavior, associated with an 11% reduction of the periaqueductal gray matte compared to the non-GA group [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This scrutiny involved a total of 2,647,648 children as participants across various age groups. The studies were conducted across multiple geographical locations, including the Egypt (Bakri et al, 2015), Japan (Kobayashi et al, 2020), United States (Backeljauw et al, 2015;Bartels et al, 2009;DiMaggio et al, 2011;Flick et al, 2011;Hu et al, 2017;Nestor et al, 2017;Sprung et al, 2012;Stratmann et al, 2014;Sun et al, 2012Sun et al, , 2016Warner et al, 2018Warner et al, , 2021Wilder et al, 2009;Zaccariello et al, 2019) (Bartels et al, 2009;DiMaggio et al, 2011;Hu et al, 2017;Sun et al, 2012Sun et al, , 2016Warner et al, 2018), Singapore (Bong et al, 2013), the Netherlands (de Heer et al, 2017), Taiwan (Feng et al, 2020;Ko et al, 2014Ko et al, , 2015Tsai et al, 2018;Yang et al, 2021), Sweden (Arana Håkanson et al, 2020;Castellheim et al, 2018;Glatz et al, 2017;Pikwer et al, 2023), Australia(DiMaggio et al, 2009C. H. Ing, DiMaggio, Malacova, et al, 2014;, Canada (Graham et al, 2016;O'Leary et al, 2016O'Leary et al, , 2019, Germany (Schüttler et al, 2021)<...…”
Section: Introductionmentioning
confidence: 99%